Chapter La relazione tra il costrutto di mattering e il benessere nelle sue concettualizzazioni (edonico, eudaimonico e olistico). A systematic review - PARADISI, MONICA (Studies on Adult Learning and Education, 2022)
Perception of mattering, defined as individual's feeling of being important for others (Rosenberg and McCullogh 1981), is a construct which in the recent years has received an increasing amount of attention as a factor able to improve people well-being. Individual well-being has been defined in different ways: hedonic as satisfaction with life (Diener and Lucas 1999), eudaimonic that is the feeling of realization of the proper true self (Ryff 1995), and holistic, namely the satisfaction toward different life domains (Prilleltensky et al. 2015). Given the various definitions, it was necessary to systematize this literature in order to clarify if perceived mattering is linked to well-being independently of the perspective adopted by researchers to conceptualize this construct. Therefore, a systematic review, following the PRISMA statement, was conducted. The final number of included studies was 39 (22 hedonic, 9 eudaimonic and 9 holistic well-being). Almost all the studies reported a positive association between mattering and well-being except for some differences due to participants' gender or cultural background. Results indicated the positive role of mattering in promoting well-being independently from the conceptualization adopted.